The Mediating Role of Performance Measurement System in the Relationship between Information Technology Capabilities and University Performance - Suryo Pratolo; Diandra Talita Spama; Hafiez Sofyani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
To improve performance, higher education institutions (HEIs) have attempted to formulate performance measurement system (PMS) policy and information technology (IT) development. The purpose of this study is to examine the role of IT capability on financial performance and operational performance of private HEIs in Indonesia through PMS implementation as mediating variable. Using purposive sampling method, 149 questionnaire responses obtained from private HEIs located on Java Island, Indonesia. The respondents are head of human resource and finance department and person in charge of technology and information systems in the sample universities. The data were analysed using the Structural Equation Modelling (SEM) method. This study found that IT capabilities were only associated with both financial and operational performance indirectly through PMS implementation. Thus, this study confirmed that PMS played a role as mediating variable. This study contributes to the develop the body of knowledge, especially related to the role of IT capabilities and PMS role in enhancing both the financial and operational performance of HEIs. Practically, this research provides beneficial suggestions for HEI management to improve HEI performance.